Molecular characterization and phylogenetic analysis of betasatellite molecules associated with okra yellow vein mosaic disease in Sri Lanka - Jeyaseelan, T.C.; Jeyaseelan, E.C.; Costa, D.M.D. (University of Jaffna, 2018)
Okra production in Sri Lanka has been severely affected by okra yellow vein mosaic disease (OYVMD), which is caused by begomoviruses and associated betasatellites. These betasatellite molecules commonly determine the development and severity of the disease. Therefore, knowledge about the genetic variability of betasatellites associated with OYVMD could assist okra breeding programs in the selection of resistant varieties. The present study aimed to characterize the betasatellite DNA sequences associated with OYVMD in Sri Lanka and to determine their phylogenetic relationships. Betasatellite DNA of six virus isolates from widely separated geographical locations were sequenced and compared with already reported begomovirus betasatellites. The betasatellite molecules have features common to other betasatellite DNAs: a conserved nonanucleotide TAATATTAC, a coding sequence for the protein βC1, an adenine rich region and a satellite conserved region. Nucleotide diversity among the isolates was relatively low (π = 0.034). A recombination event was detected at a specific region in the genome of all isolates. The isolates shared >96% sequence identity with bhendi yellow vein betasatellites reported from India and phylogenetic analysis confirmed their genetic relationship.
Keywords: abelmoschus esculentus; begomovirus; plant virus; virus recombination